2016
DOI: 10.17577/ijertv5is030361
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Experimental Investigation and Optimization of Process Parameters in Drilling Mild Steel with HSS Drill Bit using Taguchi Method

Abstract: The primary objective of this paper is to make a review of literature on Optimization of Cutting Parameters in Drilling mild steel using Taguchi Methodology to obtain minimum surface roughness. The settings of the parameters were made by using Taguchi's orthogonal array for performing the experiment. Analysis of variance (ANOVA), signal to noise (S/N) ratio, regression analysis were employed by the various researchers to find out the optimal value by investigating the effects of the cutting parameter. It has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…This work also deals with the removal of these abnormalities such as the burr, coolant pressure, feed rate etc. The sequence of the operations in VMC for crankshaft has been listed below Bhargab Kalita et al [1] reviewed the experimental investigation and optimization of process parameters in drilling mild steel with HSS drill bit using Taguchi Method Methodology to obtain minimum surface roughness. It has been observed that the minimum surface roughness of a machined workpiece is influenced by several process Impact Factor (JCC): 7.6197 SCOPUS Indexed Journal NAAS Rating: 3.11 parameters such as spindle speed, feed rate, cutting fluid, drill tool diameter etc.…”
Section: Introductionmentioning
confidence: 99%
“…This work also deals with the removal of these abnormalities such as the burr, coolant pressure, feed rate etc. The sequence of the operations in VMC for crankshaft has been listed below Bhargab Kalita et al [1] reviewed the experimental investigation and optimization of process parameters in drilling mild steel with HSS drill bit using Taguchi Method Methodology to obtain minimum surface roughness. It has been observed that the minimum surface roughness of a machined workpiece is influenced by several process Impact Factor (JCC): 7.6197 SCOPUS Indexed Journal NAAS Rating: 3.11 parameters such as spindle speed, feed rate, cutting fluid, drill tool diameter etc.…”
Section: Introductionmentioning
confidence: 99%